Impact of Hemodialysis on Gasdermin D and Vanin 1 Among Patients With Chronic Kidney Disease - Kazem Abdullah, Mohmmed; Rifaat Sarhat, Entedhar (Journal of Neonatal Surgery, 2025)
Chronic kidney disease is a progressive disorder defined by structural and functional abnormalities in the kidneys, irreversible renal function impairment. An estimated glomerular filtration rate (eGFR) of less than 60 mL/min per 1·73 m², an albumin creatinine ratio (ACR) of ≥ 30 mg/g, or indicators of damage to the kidneys, like albuminuria, hematuria, or abnormalities found through laboratory tests or imaging, that persist for at least three months. The aim of this study was to investigate the impact of hemodialysis on Gasdermin D and Vanin 1 among patients with chronic kidney disease CKD. The study included 30 control samples and 60 patients with CKD who underwent regular hemodialysis in dialysis centers in Baquba Teaching Hospital and Baladruz General Hospital (30 sample pre dialysis and 30 sample post dialysis). (5 ml) of the blood sample were collected, to determine biochemical markers Gasdermin D and Vanin 1 by using an Enzyme Immunoassay (ELISA) kit. The current study showed a significant increase in all the measured parameters in patients with CKD when compared to control group. the highest levels of Gasdermin D in the pre-dialysis group (1.93 ± 0.40 ng/ml), post-dialysis (1.25 ± 0.24 ng/ml), and the lowest levels in the control group (0.75 ± 0.34 ng/ml) with (p-value <0.001). And Vanin 1 the pre-dialysis group had significantly elevated levels (1162.02 ± 147.61 ng/L) compared to post-dialysis (841.36 ± 131.16 ng/L) and control groups (524.58 ± 165.79 ng/L). blood urea in the pre-dialysis group (92.96 ± 17.58 mg/dl), post-dialysis group (47.61 ± 7.40 mg/dl) and the control group (26.97 ± 5.21 mg/dl) (p<0.001). And Serum creatinine pre-dialysis levels (6.64 ± 1.76 mg/dl), post-dialysis levels (3.26 ± 0.85 mg/dl) and control levels (0.71 ± 0.11 mg/dl) (p<0.001). Whereas The pre-dialysis group (4.58 ± 0.93 mg/dl), post-dialysis group (2.83 ± 0.79 mg/dl), and the control group (4.11 ± 0.98 mg/dl)..